MENYOAL ASURANSI KONVENSIONAL VERSUS ASURANSI SYARIAH - Thohari, Fuad (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2011)
Insurance is a contract (agreement) between the insured risk coverage with the insurer. The insurer promises to pay any damages caused to the insured. Some Muslims argue, insurance allowed in all its forms; others refuse completely; others receive only for some forms of insurance. Arguments are built where modern insurance contract becomes invalid in the perspective of Islamic law. It must be determined various religious and ethicalconsiderations, for example: the prohibition of ribâ (interest), the prohibition of gharâr (uncertainty), maysir (speculative), and other problems.DOI: